Preparation of Copper Oxide Nanostructure Thin Film For Carbon Monoxide Gas Sensor - Brian Yuliarto (Molekul, 2016)
This work reports the synthesis of nanostructure of CuO thin film using dip coating and chemical bath deposition method. Seed layer was deposited by dip coating method using zinc nitrate as a precursor. The CuO nanostructure has successfully grown on CBD process at 95oC for 6 hours. The X Ray Diffraction characterization result shows that the CuO has monoclinic crystallization and good crystallinity. Moreover, the Scanning Electron Microscope characterization results  shows that CuO has nanospike-like shape. The CuO thin film as a gas sensor shows relatively high response on CO gas at the temperature working above 200oC. The highest response is obtained at 350oC of working temperature toward 30 ppm CO gas at 186% of sensor response.